Pengaruh Motivasi, Lingkungan Keluarga dan Pendidikan Terhadap Minat Berwirausaha Mahasiswa Jurusan Akuntansi Reguler - Putri Dea Giantari, Ni Luh; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 28 No 1 (2019)DO - 10.24843/EJA.2019.v28.i01.p01, 2019)
This research was conducted to determine the effect of motivation consisting of career motivation and economics, family environment, accounting education and entrepreneurship education towards the interest in entrepreneurship in regular accounting majors at the Faculty of Economics and Business, Udayana University. The population in this study were students of regular accounting majors, Faculty of Economics and Business, Udayana University class of 2015. Methods: Determination of samples using saturated sampling techniques. The sample in the study amounted to 142 people. The method of data collection is a survey method with a questionnaire. The data analysis technique is the classic assumption test and multiple linear regression analysis. Based on the results of the analysis it was found that motivation which included career motivation and economics, family environment, accounting education, and entrepreneurship education had a positive effect on the interest in entrepreneurship in regular accounting majors. Keywords : Motivation, Environment, Education, Interest, Entrepreneurship.